Tracking the origins of plastic debris across the Coral Sea: A case study from the Ouvéa Island, New Caledonia. Issue 1 (15th August 2015) - Maes, Christophe; Blanke, Bruno
Highlights: Addressing the surface drift of plastic debris in the Coral Sea, southwest Pacific. Calculation of pathways explaining successfully the journey of two plastic bottles. Estimates of Lagrangian transfer times based on numerical models. Meridional currents, meso and submesoscale activity contribute to the drift of debris. Abstract: Contamination of the marine environment by human-made plastic litter is a growing and global problem. Our study attempts to explain the presence of two plastic bottles beached on the Ouvéa Island, in the southwest Pacific Ocean, with trademarks from the Solomon Islands and Papua New Guinea (PNG). We simulate the oceanic drift tracks and associated transit times with a Lagrangian interpretation of the surface currents of a high-resolution ocean model. Our results show that it takes less than 2–3 months for drifting objects to connect these archipelagos (New Caledonia, Solomon Islands and PNG) and highlight the role of the meridional component of the circulation rather than the dominant zonal jets. This study shows that the origin or traceability of trash represent valuable information that can be used to test and, ultimately, improve our understanding of ocean circulation.